2013
DOI: 10.1007/s13105-013-0271-6
|View full text |Cite
|
Sign up to set email alerts
|

The senescence-accelerated mouse prone-8 (SAM-P8) oxidative stress is associated with upregulation of renal NADPH oxidase system

Abstract: Herein, we investigate whether the NADPH oxidase might be playing a key role in the degree of oxidative stress in the senescence-accelerated mouse prone-8 (SAM-P8). To this end, the activity and expression of the NADPH oxidase, the ratio of glutathione and glutathione disulfides (GSH/GSSG), and the levels of malonyl dialdehyde (MDA) and nitrotyrosine (NT) were determined in renal tissue from SAM-P8 mice at the age of 1 and 6 months. The senescence-accelerated-resistant mouse (SAM-R1) was used as control. At th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Incidentally, the serum levels found in the SAMP8 mice were always lower, independently of the treatment method. We may speculate that senescence alterations reported in SAMP8 kidney and liver may influence hPi metabolism (Baltanás et al, 2013;Bayram et al, 2013). However, this aspect is out of the scope of this work.…”
Section: Serum and Hippocampus Proinsulin Levelsmentioning
confidence: 82%
“…Incidentally, the serum levels found in the SAMP8 mice were always lower, independently of the treatment method. We may speculate that senescence alterations reported in SAMP8 kidney and liver may influence hPi metabolism (Baltanás et al, 2013;Bayram et al, 2013). However, this aspect is out of the scope of this work.…”
Section: Serum and Hippocampus Proinsulin Levelsmentioning
confidence: 82%
“…All these induced a consequent increase in inflammationmediated signals (Calabrese et al, 2011b;Scuto et al, 2019). A few studies have found that oxidative stress (Baltanaś et al, 2013), high levels of inflammation (Ren et al, 2018), activated microglias and astrocytes (Chen et al, 2018) were found in brain tissue of SAMP8 mice, especially the hippocampus. Rb1 and Rg1 were the active ingredients of the root of Panax ginseng C. A. Mayer, which have anti-inflammatory and anti-oxidative stress pharmacological effects (Hui et al, 2017;Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In old rats, renal ROS, dysfunction, and structural injury as well as cell senescence markers are increased compared to the young and associated with overexpression of NOX4 and p22phox in the kidney (Simao et al, 2011). The senescence-accelerated mouse prone-8 (SAMP8) shows higher levels of renal NOX2 expression and NADPH oxidase activity at the age of 1 month than the senescence-accelerated-resistant mouse (Baltanas et al, 2013).…”
Section: Common Mechanisms Of Cardiac and Renal Agingmentioning
confidence: 99%